2016
DOI: 10.1016/j.vph.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence for a role of the transient receptor potential canonical 3 (TRPC3) channel in endoplasmic reticulum stress-induced apoptosis of human coronary artery endothelial cells

Abstract: Unresolved endoplasmic reticulum (ER) stress, with the subsequent persistent activation of the unfolded protein response (UPR) is a well-recognized mechanism of endothelial cell apoptosis with a major impact on the integrity of the endothelium during the course of cardiovascular diseases. As in other cell types, Ca2+ influx into endothelial cells can promote ER stress and/or contribute to mechanisms associated to it. In previous work we showed that in human coronary artery endothelial cells (HCAECs) the Ca2+-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…For example the channels TRPC1[100, 101], TRPV1 [102-109], and TRPC6[110] are expressed at both the ER membrane as well as in the plasma membrane and have been linked to ER Ca 2+ homeostasis. Further, the channels TRPC3 and TRPC6 have each been identified as having a role in ER stress-induced apoptosis [111, 112]. Together it can be acknowledged that TRP channels have a role in maintaining ER Ca 2+ homeostasis and disruption of channel function leads to ER stress.…”
Section: Er Stress and Trp Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example the channels TRPC1[100, 101], TRPV1 [102-109], and TRPC6[110] are expressed at both the ER membrane as well as in the plasma membrane and have been linked to ER Ca 2+ homeostasis. Further, the channels TRPC3 and TRPC6 have each been identified as having a role in ER stress-induced apoptosis [111, 112]. Together it can be acknowledged that TRP channels have a role in maintaining ER Ca 2+ homeostasis and disruption of channel function leads to ER stress.…”
Section: Er Stress and Trp Channelsmentioning
confidence: 99%
“…Within mouse epithelial cells from pancreatic and parotid acini, the loss of TRPC3 function ameliorates ER stressed induced UPR via PERK signaling [114]. ER stress can cause the activation of Ca 2+ /calmodulin-dependent protein kinase II (CAMKII) and work done in HCAECs has shown Ca 2+ influx by TRPC3 is required for the activation of CAMKII within UPR and the eventual ER-stress induced apoptosis [111, 115, 116]. It has also been shown that canonical transient receptor potential-6 (TRPC6) is expressed in the ER membrane blood platelets [110] and in podocytes and the channel can be activated by albumin [112].…”
Section: Er Stress and Trp Channelsmentioning
confidence: 99%
“…In this model, advanced atherosclerotic plaques (16 weeks old) displayed larger size and increased macrophage content as compared to non‐transgenic littermates (Smedlund et al, ); moreover, endothelial inflammation was noticeable already in the early lesions only in TRPC3‐overexpressing mice (Smedlund et al, ). Furthermore, constitutive TRPC3‐mediated Ca 2+ influx triggers the unfolded protein response (UPR) in HCAEs and, in doing so, enhances their susceptibility to ER stress‐induced apoptosis (Ampem, Smedlund, & Vazquez, ). This finding is consistent with the notion that many pro‐atherogenic factors promote cause ER stress and consequently activate the UPR in an attempt to restore ER homeostasis (Tabas, ).…”
Section: Introductionmentioning
confidence: 99%
“…Apoe knockout mice, a unique mouse model of atherosclerosis, with endothelial-specific overexpression of human TRPC3 exhibited increased size and cellularity of advanced atherosclerotic lesions ( 32 ), supporting a pro-atherogenic role of endothelial TRPC3. Additionally, a previous study reported that TRPC3 is required for EC apoptosis induced by endoplasmic-reticulum stress ( 33 ). Therefore, the present study hypothesized that miR-454-3p may exert its anti-apoptotic effect by suppressing TRPC3.…”
Section: Discussionmentioning
confidence: 99%